Loneliness in Bereavement: Measurement Matters - Vedder, Anneke; Stroebe, Margeret S.; Schut, Henk A.W.; Boerner, Kathrin; Stokes, Jeffrey E.; Boelen, Paul A. (Frontiers in Psychology, 2021)
The role of loneliness in the bereavement experience has been reported as substantial, with the death of a close person leaving a considerable void in the life of the bereaved. Yet, there is lack of agreement about its precise role and, notably, whether loneliness should be included as a core symptom for diagnosis of grief complications. The ongoing threat of heightened social isolation due to the COVID-19 pandemic underlines the need to understand the impact of loneliness, and to accurately chart its prevalence, intensity, duration, and associated difficulties in the context of bereavement. Assessment issues are central to this endeavor. In this article, we review the scientific literature to examine how loneliness after bereavement has been operationalized and measured. Sixty-three articles analyzing 51 independent datasets were reviewed. Results show major disparities: approximately half of the projects assessed loneliness by means of one of two validated scales (spanning different versions); the remainder included only single- or few-item measures. Diverse instructions, content and answer categories were used. While one size does not fit all, awareness of assessment options and dis/advantages may aid selection of the most appropriate measure, to suit the goals of a particular study and the specific groups under investigation. Our conclusion is that, in selecting a loneliness measure, health care professionals should come to their own well-informed decision, aided by the information provided in our review.